Childhood trauma, BDNF Val66Met and subclinical psychotic experiences. Attempt at replication in two independent samples. (December 2016) - de Castro-Catala, Marta; van Nierop, Martine; Barrantes-Vidal, Neus; Cristóbal-Narváez, Paula; Sheinbaum, Tamara; Kwapil, Thomas R.; Peña, Elionora; Jacobs, Nele; Derom, Catherine; Thiery, Evert; van Os, Jim; van Winkel, Ruud; et al.
Abstract: Childhood trauma exposure is a robust environmental risk factor for psychosis. However, not all exposed individuals develop psychotic symptoms later in life. The Brain-derived neurotrophic factor ( BDNF ) Val66Met polymorphism (rs6265) has been suggested to moderate the psychosis-inducing effects of childhood trauma in clinical and nonclinical samples. Our study aimed to explore the interaction effect between childhood trauma and the BDNF Val66Met polymorphism on subclinical psychotic experiences (PEs). This was explored in two nonclinical independent samples: an undergraduate and technical-training school student sample (n = 808, sample 1) and a female twin sample (n = 621, sample 2). Results showed that childhood trauma was strongly associated with positive and negative PEs in nonclinical individuals. A BDNF Val66Met x childhood trauma effect on positive PEs was observed in both samples. These results were discordant in terms of risk allele: while in sample 1 Val allele carriers, especially males, were more vulnerable to the effects of childhood trauma regarding PEs, in sample 2 Met carriers presented higher PEs scores when exposed to childhood trauma, compared with Val carriers. Moreover, in sample 2, a significant interaction was also found in relation to negative PEs. Our study partially replicates previous findings and suggests that some individuals are more prone to develop PEs following childhood trauma because of a complex combination of multiple factors. Further studies including genetic, environmental and epigenetic factors may provide insights in this field. Highlights: Association between childhood trauma and subclinical psychotic experiences. BDNF Val66Met polymorphism moderate this association (G x E). Possible involvement of sex in the G x E interaction on psychotic experiences.